Characterization of pyroplastics from the North Atlantic - Dominguez-Hernandez, Cristopher; Vega-Moreno, Daura; Villanova-Solano, Cristina; Hernandez-Sanchez, Cintia; Lambre, Maria Elisa; Hernandez-Borges, Javier (Marine Pollution Bulletin, 2024)
This work describes for the first time the presence of pyroplastics in the Canary Islands (Spain). A total of 300 pyroplastics, identified between 2021 and 2024 in three beaches of the island of Tenerife, present mainly grey and dark colors, a mean weight of 6.8 +/- 13.4 g and mean dimensions of 34.2 +/- 17.0 mm (X), 24.5 +/- 12.2 mm (Y) and 14.4 +/- 6.4 (Z). A wide variety of encapsulated and semi-encapsulated materials were also found in the pyroplastics matrix, such as rocks, wood, charcoal and unmelted plastic inclusions. Fourier-transform infrared spectroscopy analysis revealed that polyethylene and polypropylene were the main types of plastic found, 61.3 % and 33.6 %, respectively. However, an important number of pyroplastics composed of more than one polymer were also found, coexisting even mixtures of polyester and polyethylene or polyethylene and styrene-ethylene-butylene-styrene in the same matrix. X-ray fluorescence spectroscopy analysis revealed the presence of a wide range of elements, being remarkable the high concentration of some heavy metals such as Pb and Cr, registering mean concentration values of 205.3 +/- 6.3 mg center dot kg(-1) and 51.1 +/- 8.9 mg center dot kg(-1), respectively. A good correlation was also found for these two metals in a total of 22 pyroplastics, which could be indicative of the presence of PbCrO4 as additive, widely used in the plastic industry for its bright yellow color, but currently regulated and restricted due to its harmful effects on human and environment health. Also noteworthy is the large variety of remains of marine organisms identified attached to the surface of the pyroplastics, such as algae, bryozoans, arthropods and molluscs, among others, which could indicate that these formations may act as a transport vector for such marine organisms. 11 1,445 5,8 Q1 Q1 SCIE 11,0